2016
DOI: 10.1007/s10531-016-1217-4
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of semi-natural grasslands, a success for phytophagous beetles (Curculionidae)

Abstract: Semi-natural pastures have rich plant and animal communities of high conservation value which depend on extensive management. As the area of such land decreases, abandoned semi-natural grasslands have been restored to re-establish biodiversity. Restoration schemes, which include thinning of woody plants and reintroduction of grazing, are mainly designed according to the responses of well-studied groups (such as vascular plants and birds). Weevils (Curculionidae) are a very diverse phytophagous beetle family. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…We also found higher abundance of herbivorous Curculionidae in fallow fields than other land uses during spring, which suggests that fallow fields provide optimal levels of springflowering weed or host plant resources for this family (Hangay and Zborowski 2010). This result is consistent previous studies which found high abundance of specialist Curculionidae species in grazed pastures (Bat ary et al 2007, Steiner et al 2016, with the probability of occurrence for certain species increasing with grassland cover (Bat ary et al 2007). More research is needed to identify plant-species associations that may be driving high Curculionidae abundance when fallowing farmlands.…”
Section: Spatio-temporal Fluctuations Of Different Beetle Groupssupporting
confidence: 91%
See 1 more Smart Citation
“…We also found higher abundance of herbivorous Curculionidae in fallow fields than other land uses during spring, which suggests that fallow fields provide optimal levels of springflowering weed or host plant resources for this family (Hangay and Zborowski 2010). This result is consistent previous studies which found high abundance of specialist Curculionidae species in grazed pastures (Bat ary et al 2007, Steiner et al 2016, with the probability of occurrence for certain species increasing with grassland cover (Bat ary et al 2007). More research is needed to identify plant-species associations that may be driving high Curculionidae abundance when fallowing farmlands.…”
Section: Spatio-temporal Fluctuations Of Different Beetle Groupssupporting
confidence: 91%
“…, Steiner et al. ), with the probability of occurrence for certain species increasing with grassland cover (Batáry et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The sika deer ( Cervus nippon ) population, which has increased since the 1980s in Japan, has caused a decrease due to grazing in grassland specialist species in grassland communities (Otsu, Hoshino & Matsuzaki, 2011). Furthermore, the total grassland area, which had covered 50% to 70% of Japan’s total land area in the 1650s, decreased to less than 1% by the early 2000s (Ogura, 2006) because of abandonment and conversion in land use, which are common with European regions (Steiner et al, 2016). Such grassland decrease in Japan had never been occurred during past 100, 000 years (Yamaura et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The sika deer (Cervus nippon) population, which has increased since the 1980s in Japan, has caused a decrease due to grazing in grassland specialist species in grassland communities (Otsu, Hoshino & Matsuzaki, 2011). Furthermore, the total grassland area, which had covered 50% to 70% of Japan's total land area in the 1650s, decreased to less than 1% by the early 2000s (Ogura, 2006) because of abandonment and conversion in land use, which are common with European regions (Steiner et al, 2016). Such grassland decrease in Japan had never been occurred during past 100000 years (Yamaura et al, 2019).…”
Section: Introductionmentioning
confidence: 99%